The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1158/1535-7163.mct-20-0476
|View full text |Cite
|
Sign up to set email alerts
|

Robust Antitumor Activity and Low Cytokine Production by Novel Humanized Anti-CD19 CAR T Cells

Abstract: Recent studies have described the remarkable clinical outcome of anti-CD19 chimeric antigen receptor (CAR) T cells in treating B-cell malignancies. However, over 50% of patients develop lifethreatening toxicities associated with cytokine release syndrome which may limit its utilization in low-resource settings. To mitigate the toxicity, we designed a novel humanized anti-CD19 CAR T cells by humanizing the framework region of single-chain variable fragment (scFv) derived from a murine FMC63 mAb and combining it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Research has shown that a murine single-chain variable fragment (scFv) in the CAR structure causes an HLA-restricted T-cell-mediated immune response, 7 resulting in the disappearance or loss of CAR-T cells. A preclinical study by Dwivedi et al 8 revealed that a humanized scFv generated by altering the CAR framework or non-complementarity-determining region reduced the immunogenicity of CAR, thereby reducing cytokine release and enhancing antitumor efficacy. However, the immunity to CAR is associated with treatment failure in some, not all clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that a murine single-chain variable fragment (scFv) in the CAR structure causes an HLA-restricted T-cell-mediated immune response, 7 resulting in the disappearance or loss of CAR-T cells. A preclinical study by Dwivedi et al 8 revealed that a humanized scFv generated by altering the CAR framework or non-complementarity-determining region reduced the immunogenicity of CAR, thereby reducing cytokine release and enhancing antitumor efficacy. However, the immunity to CAR is associated with treatment failure in some, not all clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…Of 43 B‐ALL patients, 21 were relapsed B‐ALL, 17 were refractory B‐ALL with persistent MRD positivity, and five patients were referral cases with no available clinical details. Among them, 25 received blinatumomab, eight received indigenously developed anti‐CD19‐CAR‐T, 41 and in 10 patients, BM assessment was performed pre‐anti‐CD19 immunotherapy. Among the 25 patients on blinatumomab, MRD analysis was performed on samples after 33–35 days (37 samples), 75–77 days (46 samples), and 204 days (2 samples) of starting therapy.…”
Section: Resultsmentioning
confidence: 99%
“…Surprisingly, none of the individuals required tocilizumab therapy or admission to ICUs 58 . In addition, some studies have also emphasized the application of humanized or fully human scFvs to improve the safety and efficacy of CAR‐T cell therapy 59,60 . Affinity‐tuned CAR designs, therefore can potentially aid CAR‐T cells operate within their therapeutic window while minimizing on‐target/off‐target toxicity.…”
Section: Proposed Solutions To Circumvent Drawbacks and Drive Car‐t T...mentioning
confidence: 99%